Components of Interest and Professional Thinking in Future Teachers (International Journal of Psychosocial Rehabilitation, 2020)
The article highlights the theoretical foundations, methodological principles, and results of empirical research, highlighting the importance of a culture of thinking and pedagogical communication based on the development of a step-by-step program for the formation of professional interest in future teachers. During the research, pedagogical and psychological aspects of professional thinking of students in the field of pedagogical education were identified. Our developmental authoring program has served as an important practical impetus for the development of professional thinking of future teachers.